2011
DOI: 10.1292/jvms.10-0212
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentration and Cardiovascular Effects of Lidocaine during Continuous Epidural Administration in Dogs Anesthetized with Isoflurane

Abstract: ABSTRACT. The cardiovascular effects of continuous epidural administration (CEA) of lidocaine were investigated in anesthetized dogs. Loading epidural injections of 2, 4, or 6 mg/kg of lidocaine were followed by CEA with 1, 2, or 3 mg/kg/hr lidocaine, respectively, for 2 hr under 2.0% isoflurane anesthesia. Heart rate, direct blood pressure, cardiac index, and stroke volume decreased dose-dependently during CEA, whereas systemic vascular resistance did not significantly differ with dose, and no characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
1
1
1
Order By: Relevance
“…However, it appeared that the liver gradually degraded the lidocaine and maintained its blood concentration at a constant level. Further, the serum lidocaine concentration in this experiment was lower than that in the previous experiments with dogs administered with 2% lidocaine in the epidural space (2.4 μg/ml at 30 min) [27]. Propofol used in TIVA is degraded by hepatic cytochrome P450 (CYP) 3A4 [12] and lidocaine by CYP 3A4 or 1A2 [22], but propofol is not known to inhibit the lidocaine metabolism [20].…”
Section: Discussioncontrasting
confidence: 51%
“…However, it appeared that the liver gradually degraded the lidocaine and maintained its blood concentration at a constant level. Further, the serum lidocaine concentration in this experiment was lower than that in the previous experiments with dogs administered with 2% lidocaine in the epidural space (2.4 μg/ml at 30 min) [27]. Propofol used in TIVA is degraded by hepatic cytochrome P450 (CYP) 3A4 [12] and lidocaine by CYP 3A4 or 1A2 [22], but propofol is not known to inhibit the lidocaine metabolism [20].…”
Section: Discussioncontrasting
confidence: 51%
“…Naganobu et al (14) reported that epidural administration of morphine and fentanyl in dogs anesthetized with sevofl urane induced statistically signifi cant decreases in diastolic and mean arterial blood pressure values. A study conducted by Sakonju (15) investigated the effects of continuous epidural administration of lidocaine (3 mg/kg) in dogs anesthetized with isofl urane and they found that HR and MAP signifi cantly decreased immediately after epidural administration of lidocaine. Vnuk et al (16) showed that epidural administration of lidocaine (4 mg/kg) in dogs under isofl urane anesthesia had no signifi cant changes on HR and MAP.…”
Section: Fig 1 Cortisol Levels In Fentanyl and Lidocaine Groupsmentioning
confidence: 99%
“…Essa diminuição, embora clinicamente insignificante (Tab. 1), pode ser creditada à lidocaína, fato esse também observado porSakonju et al (2011), que, após a administração de lidocaína 2% no volume de 0,2mL/kg pela via epidural, verificaram diminuição da PA em cães.…”
unclassified